Constructing the Cocyclic Structures for Crossed Coproduct Coalgebras (Communications in Mathematical Research, 2021)
In this paper, we construct a cocylindrical object associated to two coalgebras and a cotwisted map. It is shown that there exists an isomorphism betweenthe cocyclic object of the crossed coproduct coalgebra induced from two coalgebraswith a cotwisted map and the cocyclic object related to the diagonal of the cocylindrical object.